Penghitungan Efisiensi Pelatihan dengan Return on Training Invesment - Abraham, Irfan (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This article aims to provide a more complete and comprehensive picture of training program evaluation. The method used in writing is descriptive analysis. That currently most people want a more complex and different differentiation of training evaluation. Return on Training Investment can provide an alternative in calculating the impact of training conducted by an institution or company.